PROTOTIPE PENYIRAMAN OTOMATIS AIR DAN PUPUK MENGGUNAKAN ARDUINO DENGAN METODE FUZZY LOGIC BERBASIS WEBSITE PADA TOKO REZEKI SUMBER POT - Pratama, Rivan Dwi; Utama, Gunawan Pria; Chandra, Joko Christian; Kusumaningsih, Dewi (Universitas Budi Luhur, 2023)
The use of automated technology has advanced enough that routine tasks can now be performed automatically because people don't always follow rules. Automation can be used to assist ordinary jobs if they can be performed continuously regardless of the passage of time. We can utilize this contemporary technology in the fields of plantations and agriculture to get far better outcomes and maximize time efficiency. Small computers are the latest technical advances that can assist humans in carrying out routine tasks. The name of this device is microcontroller. To produce intelligent internet of things based tools that will facilitate plant care in the future, this research set out to do just that (IOT). So that it can be used in plant maintenance, especially for the maintenance of aglaonema plants which can monitor automatically whenever and wherever we are, whether we are still working, sleeping, or on vacation. A device for watering plants in a greenhouse made with a microcontroller embedded fuzzy logic system in the form of a multi-system, with three inputs for soil moisture fuzzy sets and temperature fuzzy sets for the surrounding environment. The tool can operate according to the requirements of the fuzzy logic method by carrying out routine tests. We can make a prototype that can water the plants automatically and monitor the level of soil moisture and temperature coming from the sensor via the internet using the Arduino microcontroller along with sensors such as the YL-69 soil moisture sensor and the DHT11 temperature sensor. The results of the plant watering prototype show that it can operate effectively based on a predetermined schedule and soil moisture value limit. The prototype will water at 07:00 and 17:00 and will water liquid fertilizer at 08:00 and 18:00 if the soil moisture reading is greater than 700. Electricity must flow through this device